Estonia's success and Chile's failure: A comparative analysis of cryptocurrency regulations and the impact on anti money laundering in Estonia and Chile - Valdez, Monet (DESC - Direito, Economia e Sociedade Contemporânea, 2020)
This Article is a critical analysis of the lack of cryptocurrency regulations in Chile and offers gains Chile may have by implementing Estonia’s pro-cryptocurrency approach. Additionally, the absence of regulations in Chile is examined through the comparative lens of Chile and Estonia’s global ranking in anti-money laundering. Part A begins with a brief introduction to blockchain and financial technology. Parts B and C will discuss Estonia’s and Chile’s existing crypto attitudes. Part D will include recent histories of anti-money laundering efforts of both Estonia and Chile. Part E will assess other factors that may also be impacting Estonia’s decrease and Chile’s increase in economic crimes — like money laundering. Finally, Part F will discuss whether a “one size fits all” approach works, and, particularly, if Estonia’s success could transfer to a high-risk country like Chile through the adoption of pro-cryptocurrency legislation.